Time-frequency parameters of heart-rate variability. - Van Steenis, H.G.
We have evaluated a new method to compute time-frequency parameters from cardiovascular time series. Apart from calculating the IA and the IF, characteristics of the oscillatory and irregular periods can be quantified that may be relevant to further unravel the situational- and state-dependent dynamics of homeostatic cardiovascular control processes. As a first approach, the method was applied to describe changes in time-frequency parameters and in the characteristics of the oscillatory and irregular periods from supine to standing posture, under steady-state conditions in healthy subjects. The parameters and characteristics discriminated differentially between supine rest and orthostatic challenge. Furthermore, the method can be applied to other cardiovascular time series provided they are monocomponent.
Keywords: ECG; FIR filter; Fourier transform; Hilbert transform; Nyquist frequency; R-waves.; Wigner-Ville distribution; Band-limited signals; Bandpass filtering; Cardiovascular time series; Decimation factor; Heart-rate variability; Homeostatic cardiovascular control processes; Instantaneous amplitude; Instantaneous frequency; Irregular periods; Orthostatic challenge; Oscillatory periods; Standing posture; State-dependent dynamics; Steady-state conditions; Supine posture; Time-frequency parameters